Proses Pembelajaran Anak Sekolah Minggu: suatu telaah di lingkungan gereja HKBP - Sitanggang, Serepina (JURNAL DIAKONIA, 2021)
This article is a research on the learning process of HKBP Sunday school children in District V Sumatera Timur. The purpose of this study was to determine the spirituality of Sunday school through the materials, methods and implementation of the evaluation of learning outcomes by Sunday school teachers. The method used in this paper is a qualitative-descriptive research method with interview and questionnaire techniques. The findings of this study are that learning for Sunday school children is carried out using educational elements which include the presence of Sunday school, objectives, materials, methods, and assessment of learning outcomes. The learning refers to the results of cognitive, affective, and psychomotor aspect